2019
DOI: 10.1111/jfbc.12939
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic components rich ethyl acetate fraction ofOrostachys japonicusinhibits lipid accumulation by regulating reactive oxygen species generation in adipogenesis

Abstract: In this study, Orostachys japonicus was extracted with ethyl alcohol and fractionated by a serial of organic solvents. The ethyl acetate fraction was found to be the most effective among the tested five fractions. High‐performance liquid chromatography and mass spectrometry analysis of the ethyl acetate fraction presented epicatechin gallate, quercetin‐3‐O‐glucoside, and kaempferol‐3‐O‐rutinoside. Treatment with O. japonicus inhibited reactive oxygen species (ROS) generation and lipid accumulation during adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Previous studies revealed that OJ has shown potential antioxidant, hypoglycaemic, anticancer, anti-HIV-1 protease, antiulcerogenic, analgesic, immunostimulatory, and hepatoprotective effects [ 10 12 ]. Antiadipogenic and antiobesity effects of OJ were also described previously in various in vitro and in vivo studies [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Previous studies revealed that OJ has shown potential antioxidant, hypoglycaemic, anticancer, anti-HIV-1 protease, antiulcerogenic, analgesic, immunostimulatory, and hepatoprotective effects [ 10 12 ]. Antiadipogenic and antiobesity effects of OJ were also described previously in various in vitro and in vivo studies [ 10 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 68%
“…The antiadipogenic and/or antiobesity activities of O. japonicus, R. verniciflua, G. thunbergii, and royal jelly (RJ) were individually evaluated on the cell line, animal model, or clinical trials [ 10 , 14 , 15 , 19 , 22 27 ]. In our previous studies, we found evidence that GT, RV, OJ, and RJ showed potential antiadipogenic and/or antiobesity activity in 3T3-L1 adipocytes or Sprague-Dawley Rats [ 13 , 16 , 28 – 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…The antioxidant activities showed the same pattern of the results on their phenolic contents. Antioxidant activity has a positive correlation with phenolic contents [4,25]. Based on these results, the temperatures above 70 °C applied until a complete dry state could reduce the phenolic content consequently reducing antioxidant properties.…”
Section: The Effects Of Different Drying Methods On the Antioxidant Cmentioning
confidence: 70%
“…The 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay modified and used the method by Jang et al [25]. Briefly, same volume of sample and DPPH solution (0.2 mM) were mixed and placed for 30 min at room temperature.…”
Section: Dpph Assaymentioning
confidence: 99%
See 1 more Smart Citation